Multimodal review. A new protocol for literature observation - Fabio Galli (Medicina Universitaria)
There are numerous literature review methodologies, which can be mainly divided into systematic and non-systematic. The evolution of these methodologies is constant over time, as is the innovation of the methodologies for evaluating the literature itself. Multimodal review (MR) is a new literature review method that combines several systematic and non-systematic methodologies to offer the most comprehensive and in-depth view of a topic. MR is based on a literature selection protocol with the advantage of using a broad spectrum of qualitative and quantitative data derived from literature reviews at the top of the evidence hierarchy and the use of narrative literature. This manuscript aims to propose this new methodology and its development through a theoretical presentation of the procedure of use. The MR can be considered a systematic method that allows an in-depth study of a predefined target’s clinical, scientific, human, social characteristics, and gaps.